Withania somnifera (L.) Dunal as Add-On Therapy for COPD Patients: A Randomized, Placebo-Controlled, Double-Blind Study - Singh, Priyam; Salman, Khushtar Anwar; Shameem, Mohammad; Warsi, Mohd Sharib (Frontiers in Pharmacology, 2022)
Background: The current gold standard therapies for Chronic Obstructive Pulmonary Disease (COPD) lack disease modifying potential and exert adverse side effects. Moreover, COPD patients are at higher risk of severe outcomes if they get infected by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus, the cause of current epidemic. This is the first study to document clinical research on an adaptogenic and steroidal activity-containing herb as a complementary medicine for COPD treatment. Objective: To evaluate the efficacy of Withania sominifera (WS) as add-on therapy for COPD patients. Methods: A randomized, placebo-controlled and double-blind clinical study was conducted. 150 Patients were randomly assigned to three groups: control, placebo and WS group. In addition to conventional medicines, WS root capsules or starch capsules were given twice a day to WS group or placebo group respectively. Their lung functioning, quality of life, exercise tolerance, systemic oxidative stress (OS) and systemic inflammation were assessed before and after 12 weeks of intervention. WS root phytochemicals were identified by LC-ESI-MS. The inhibitory activity of these phytochemicals against Angiotensin-converting enzyme 2 (ACE-2), the SARS-CoV-2 receptor; myeloperoxidase (MPO); interleukin-6 (IL-6) were evaluated by in-silico docking, to investigate the mechanism of action of WS. Results: The pulmonary functioning, quality of life and exercise tolerance improved; and inflammation reduced notably the most in WS group. Systemic oxidative stress subsided significantly only in WS group. Although, minor placebo effect was observed in SGRQ test but it was not present in other tests. WS roots had withanolides that showed significant inhibitory activity against ACE-2, MPO and IL-6 proteins comparable to standard drug or known inhibitor. Moreover, FEV1% predicted had significant correlation with systemic anti-oxidative status (positive correlation) and malondialdehyde (MDA, negative correlation), suggesting that anti-oxidative potential of WS has significant contribution in improving lung functioning. Conclusions: Our study demonstrated that clinically, WS root when given along with conventional drugs ameliorated COPD significantly more in comparison to conventional drugs alone, in GOLD 2 and 3 categories of COPD patients. In-silico, it has potent inhibitory activity against SARS-CoV-2 receptor, ACE-2; MPO and IL-6.